Investigation of the group differences in indoor environmental quality - Li, Zheng; Berk Kazanci, Ongun; Zhang, Qingwen; Olesen, Bjarne W. (CLIMA 2022 conference, 2022)
Based on the field measurements and questionnaires surveys carried out in 22 offices in Harbin, China, the group differences (gender, age, BMI, level of education, location groups) in human comfort for different levels of environmental parameters were investigated. It was found that males, elder subjects (above 25 years old) and the subjects with higher academic degrees have higher comfort votes than other groups. The group differences were larger in a warmer thermal environment and the differences in thermal comfort votes could be larger than 0.5 scale units on the comfort scale among gender, age and level of education groups when the temperature was higher than 26°C in summer or higher than 24°C in winter. For indoor air quality, the differences in comfort votes for air freshness were larger when the CO2 concentration was less than 960 ppm and the difference in comfort votes for air pollution was larger when PM2.5 concentration was higher than 25 μg/m3. For sound comfort, it was found that the subjects near doors had higher sensitivity to the change in sound levels than the subjects at other locations. For light comfort, the higher illuminance could cause larger group differences. This study can be used to better develop comfort systems, especially personal comfort systems.